A study of the representations supported by the orbit closure of the determinant. (24th October 2014) - Kumar, Shrawan
Abstract: We show the existence of a large family of representations supported by the orbit closure of the determinant. However, the validity of our result is based on the validity of the celebrated 'Latin square conjecture' due to Alon and Tarsi or, more precisely, on the validity of an equivalent 'column Latin square conjecture' due to Huang and Rota.